(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Biological and clinical researches lay the foundation for the evolution of medical knowledge. Their consequent application in a clinical context offers the possibility of diagnostic and therapeutic process evolution. The recent shift towards a more defensive medicine, which is encouraged by a growing amount of medico-legal issues, induces the necessity for more rigid guidelines. These clinical recommendations offer more safety to the clinician but can severely limit the scientific progress. In this context, the physician can in fact risk a possible downgrade to simple executor of medical protocols. Medicine is therefore at a crossroads between a safe application of proved therapeutic schemes and a riskier, but advised, clinical innovation.